Atlas of Dermatology, Dermatopathology and Venereology Inflammatory Dermatoses - Smoller, Bruce; Bagherani, Nooshin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Bringing together thousands of the best dermatologic clinical and pathological photographs and figures from researchers and scientists around the world, this volume focuses on the most prevalent dermatologic disorders as they relate to inflammatory dermatoses. This volume includes atypical presentations of various disorders, giving insight into differential diagnoses, helping to familiarize the reader with some of the rarest dermatologic disorders. Atlas of Dermatology, Dermatopathology and Venereology Volume 2 is written for dermatologists, dermatopathologists, and residents and summarizes data regarding any dermatologic disorder and syndrome. Each entry includes an introduction, clinical and pathological manifestations, diagnosis, differential diagnosis, and treatment and prognosis. .
Inflammatory Dermatoses -- 1. Pruritus -- 2. Eczema, Lichenification, Prurigo and Erythroderma -- 3. Atopic Dermatitis -- 4. Contact Dermatitis: Irritant -- 5. Contact Dermatitis: Allergic -- 6. Urticaria and mastocytosis -- 7. Immunobullous Dermatoses -- 8. Psoriasis -- 9. Lichen Planus and Lichenoid Disorders -- 10. Disorders of Connective Tissue -- 11. Disorders of Skin Color -- 12. Disorders of the Sebaceous Glands -- 13. Rosacea, Perioral Dermatitis and Similar Dermatoses, Flushing and Flushing Syndromes -- 14. Disorders of Sweat Glands -- 15. Subcuatneous Fat -- 16. The (3z(BConnective Tissue Diseases(3y (B-- 17. Purpura and Microvascular Occlusion -- 18. Vasculitis and Neutrophilic Dermatoses and Related Disorders -- 19. Necrobiotic Disorders -- 20. Sarcoidosis -- 21. Systemic Disease and the Skin -- 22. The Skin and the Nervous System -- 23. Psycho-Neuro-Endocrine-Immune Dermatology (PNEI Dermatology) -- <24. Psychocutaneous Disorders -- 25. Disorders of Nails -- 26. Disorders of Hair -- 27. The Skin and the Eyes -- 28. The Eternal Ear -- 29. The Oral Cavity and Lips -- 30. The Breast -- 31. The Genital, Perianal and Umbilical Regions -- 32. Drug Reactions -- 33. Erythema Multiforme, Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis -- 34. War-related Dermatoses -- 35. Specific Dermatoses of Pregnancy -- 36. Occupational Dermatoses -- 37. Mechanical and Thermal Injury -- 38. Cutaneous Photobiology -- 39. Diseases of the Veins and Arteries Leg Ulcers -- 40. Disorders of Lymphatic Vessels.s
Keywords: Dermatology; Pathology; Dermatology; Pathology; Skin Diseases